PENGARUH MOTIVASI EXISTENCE, RELATEDNESS, GROWTH (ERG) TERHADAP RESILIENSI PRAMUWISATA BALI PADA ERA MENUJU NEW NORMAL - Tirza Poriesti, Theresia Mardiani; Dewi, LGLK.; Dewi, NGAS. (Jurnal IPTA (Industri Perjalanan Wisata), 2022)
COVID-19 pandemic affects tourism actors, one of which is tour guides who are in direct contact with tourists. In order to survive, it is necessary to have resilience and motivation from within the Bali tour guides. This study aims to determine the characteristics and motivations of ERG possessed and the influence of these motivations on the resilience of Bali tour guides in the era towards the new normal. The sampling technique used is cluster sampling with a total of 258 Bali tour guide respondents who is living in Denpasar City. Data collection techniques using questionnaires and literature study and data analysis using simple regression method. The result show that the characteristics are dominated by male, age range 21-30 years, the last formal education is college and the length of time working is more than 4 years. In addition, there is a positive influence of motivation on resilience in the era towards the new normal where the influence of motivation as much as 2.3% on resilience, the rest is influenced by other unknown factors. Overall, the motivation variable is high, where growth needs are in the highest position and existence needs are in the lowest position, so they still need government assistance and HPI in the form of training programs. While the resilience variable is high where the equity aspect is in the highest position and the perseverance aspect is in the lowest position so it is necessary to increase the perseverance and self-discipline of Bali tour guides.